THE INFLUENCE OF BRAND IMAGE AND BRAND EXPERIENCE ON BRAND LOYALTY ON BRIZZI CARD USERS AT BRI UNIT SENTRA BISNIS DRIYOREJO - Fuad Farhan; Firman Aditya (Jurnal Ekonomi, 2019)
Technology is getting more sophisticated, all daily activities are getting easier, including in terms of transactions. Now, the so-called Brizzi Card has become popular, which is a payment instrument with the value of money stored electronically on a server or card. This Brizzi card can then be used for payment transactions on the internet and merchants who have collaborated with the Brizzi card issuing bank. Became popular because Brizzi has been intensively used to transact online and offline stores. Public facilities have introduced the Brizzi Card as payment for tolls, commuter line, trans Jakarta, parking, and many more. This research was conducted to know and analyze the effect of brand image and brand experience on brand loyalty by using multiple linear regression analysis models. The sample used in this study were 100 respondents who were owners or users of the BRIZZI card at the Driorejo BRI Business Center Unit. The results showed that all research variables consisting of brand image and brand experience had a significant effect on the variable brand loyalty. This is proven empirically from the SPSS calculation which results in the calculated F value> F table, namely 16,156> 3.09 or by looking at the significant level of 0.000 <0.05. The results also show that the brand image variable has a significant effect on brand loyalty. This is proven empirically from the SPSS calculation which results in the value of t count> t table, namely 5.055> 1.661 or by looking at the significant level of 0.000 <0.05. Meanwhile, brand experience has no significant effect on brand loyalty. This is proven empirically from the SPSS calculation which results in the value of t count <t table which is 1.086 <1.661 or by looking at the significant level of 0.280> 0.05.